2022
DOI: 10.1021/acs.jafc.2c05142
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Responses and Degradation Mechanisms of the Herbicide Diuron in Rice Crops

Abstract: Diuron [DU; 3-(3,4-dichlorophenyl)-1,1-dimethylurea], a widely used herbicide for weed control, arouses ecological and health risks due to its environment persistence. Our findings revealed that DU at 0.125–2.0 mg L–1 caused oxidative damage to rice. RNA-sequencing profiles disclosed a globally genetic expression landscape of rice under DU treatment. DU mediated downregulated gene encoding photosynthesis and biosynthesis of protein, fatty acid, and carbohydrate. Conversely, it induced the upregulation of numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…It was reported diuron could induce lipid peroxidation of the cell membrane by generating ROS, thereby leading to oxidative stress injury ( Wang et al, 2022 ). ROS, MDA, and LDH were common indicators of cellular oxidative damage ( Wakeel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported diuron could induce lipid peroxidation of the cell membrane by generating ROS, thereby leading to oxidative stress injury ( Wang et al, 2022 ). ROS, MDA, and LDH were common indicators of cellular oxidative damage ( Wakeel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Diuron (3-(3,4 dichlorophenyl)-1,1 dimethylurea) was a phenylurea herbicide that was extensively acted to Broadleaf weeds and grassy weeds in diverse crops fields such as cotton, fruit, and cereals ( Li et al, 2021 ; Wang et al, 2022 ). Its function was to block the binding sites of plastid quinones in photosynthetic system II, and then destroy electron transport, thereby leading to weed death.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide stress has been shown to be detrimental to plant growth and development. It was observed that when rice plants were treated with 0.125 mg/L of butachlor, their elongation rate, biomass and chlorophyll content decreased significantly, to only 58.3%, 46.3% and 50.5% of the untreated control [23]. The growth of onion roots was significantly reduced (p < 0.01) by 37.94% and 56.03% following treatment with 175 µg/mL and 1750 µg/mL of IMD [10].…”
Section: Pesticides Affect Plant Growth and Metabolitesmentioning
confidence: 98%
“…The expression of genes encoding calmodulin-like protein (CML) and calmodulin (CAM) proteins was strongly suppressed, as well as the expression of transcription factors belonging to the WRKY family. rice 217 diuron Five genes involved in ABA production up-regulated OsNCED4 and four AAO genes (LOC_Os03g57720, LOC_Os03g31550, and LOC_Os03g57690), which encode 9-cis-epoxycarotenoid dioxygenase (NCED) and ABA aldehyde oxidase (AAO). Brassica napus L. 218…”
Section: Abiotic Stresses Of Pesticides On Cropsmentioning
confidence: 99%